La metodología juego-trabajo en la adquisición del aprendizaje significativo en los niños de 5 a 6 años de la Unidad Educativa “8 de noviembre” de la parroquia Balsapamba, Cantón San Miguel, provincia Bolívar, en el periodo noviembre 2021-marzo 2022 - Barragán Fuentes, Carla Estefanía (2022)
The project entitled "The game-work methodology in the acquisition of meaningful learning in children from 5 to 6 years of the Educational Unit "8 de Noviembre", in which new strategies are proposed, through playful activities that facilitate the teaching-learning process, in order to achieve educational changes, through the management and implementation of new pedagogical strategies, such as the game, where children learn in a fun, dynamic and different way, thus acquiring significant learning that contributes with the development and their integral formation as human beings, it is also an innovative proposal based on real and daily events. We have a specific theoretical framework, concrete and supported by reliable bibliographic sources, created in turn by two variables of our educational project and especially in the problem that exists within the educational institution, this research has a qualitative approach, since it is focused on the collection and analysis of data, subject to an observation sheet, in addition to this it is a descriptive, exploratory and bibliographical investigation, with an inductive method since it starts from the particular to the general. Next we have the picture of the universe and sample studied in the aforementioned institution, we also have the analysis and interpretation of results, represented in tables and in cakes in order to publicize the identified problem in a concrete and precise way. It should be emphasized that play is important and essential in children's lives, in order to achieve maximum development in different areas such as: the development of intelligence, motor development, the natural and cultural environment, and the ability to communicate and relate. with others, strengthening autonomy, independence and the ability to face everyday problems